EXPLORING THE IMPACT OF INTELLECTUAL CAPITAL AND FINANCIAL PERFORMANCE ON MANUFACTURING FIRM VALUE IN INDONESIA - Verlita (Pena Cendekia Insani, 2025)
This study examines how intellectual capital and financial performance affect firm value in Indonesian manufacturing companies listed on IDX (2012-2016). Using path analysis on 35 observations from seven companies, we investigated causal relationships among variables. Results show intellectual capital does not significantly influence financial performance (ROE) or firm value (PBV). However, financial performance positively impacts firm value. Financial performance also does not mediate the intellectual capital-firm value relationship. These findings suggest investors should prioritize financial performance indicators in investment decisions, while intellectual capital's role may require alternative measurement approaches.